The Influence of Financial Literacy, FOMO Lifestyle, and Financial Attitude on Financial Management: A Case Study of University Students in Pontianak City - Dhina Citra Elvira; Fuad Ramdhan Ryanto (SAINTIS Publishing, 2025)
This study aims to analyze the influence of financial literacy, Fear of Missing Out (FOMO) lifestyle, and financial attitude on the financial management of university students in Pontianak City. The research employs a quantitative approach with an associative research design. The sample consists of 150 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression, preceded by validity and reliability tests, along with classical assumption testing. The results indicate that both financial literacy and financial attitude have a positive and significant effect on financial management, while the FOMO lifestyle has a negative and significant effect. Collectively, the three variables have a significant simultaneous impact on students' financial management. These findings highlight the importance of enhancing financial literacy, cultivating positive financial attitudes, and managing the influence of FOMO in shaping healthy financial behavior. The results underscore the need for sufficient financial knowledge and awareness to support responsible financial decision-making among students, particularly in the face of digital social pressures. The study offers practical implications for students to become more discerning in responding to social trends and emphasizes the importance of technology-based educational interventions. Future research is encouraged to explore other psychological factors that may mediate the relationships between variables, such as self-control or impulsive buying behavior.